Numerical characterization of the solar updraft tower plant by introducing parabolic chimney profile configurations for increased performance - Muhammad Saad (00000320957); Dr Naveed Ahmed (USPCAS-E, NUST, Islamabad, 2021)
TH-308
Keywords: MS-TEE Thesis